Comportamento informacional de estudantes em formação com uso das metodologias ativas de ensino aprendizagem - Barcellos, Barbara França (2019)
The active methodologies aim to encourage the student to learn in an autonomous and participative way. UFS adopts this methodology in all its health courses, in the Campus de Lagarto, and, in view of the research difficulties presented by students in training with the use of PBL, this research had, as a general objective, of the results obtained, present proposals on how to improve the skills and abilities for the autonomy in research of university students in training who use the active methodologies of teaching learning in the campus of Lagarto. The research data point out difficulties in accessing the specific sources (databases and types of specific studies) of the area of performance and of the abilities to carry out search strategy, with the use of Boolean operators, descriptors and search filters. The research presented, as an intervention proposal, an online research tutorial to assist in the accomplishment of bibliographic searches. With this product, the research also achieves the third specific objective, that of contributing to expand the students' abilities and competences in the information resources for decision making. The study is characterized as action research and exploratory research. A questionnaire was used to survey the degree of difficulty of searching for information in databases, thus configuring a qualitative-quantitative approach. The intervention site occurred at the Federal University of Sergipe, Professor Antônio Garcia Filho Campus, located in the municipality of Lagarto / SE.